The effect of within-vineyard variability in vigour and water status on carbon discrimination in Vitis vinifera L. cv Merlot - Rossouw, Gerhard C. (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MScAgric (Viticulture and Oenology))--University of Stellenbosch, 2010.